A Brief summary on Lexicographic Network Flow Problem - Paudyal, Rajendra; Adhikari, Narayan Prasad (Journal of Advanced College of Engineering and Management, 2025)
Since there have been more natural and man-made disasters in recent decades, evacuation preparation has become more important. A lexicographic network flow optimization model is one of the most effective approaches to simulating the evacuation scenario. The majority of the requirements for evacuation planning are covered by this model. Using models and solution strategies developed in this subject, this paper attempts to give an overview of lexicographic static and dynamic network flow challenges linked to evacuation planning.